Effect of Employee Competence and Perceived Organizational Support on Organizational Commitment Mediated by Employee Performance - Hendry Kurniawan (AFEBI Management and Business Review, 2022)
This study aimed to determine the effect of employee competence and perceived organizational support on organizational commitment with performance as a mediating variable. This study uses a quantitative approach. The quantitative research method aims to test the established hypotheses. The population in this study were employees of the service organization in Rokan Hulu using a total sampling technique, which means using the entire population as the research sample. In this study, researchers involved 100 employees in service organizations in Rokan Hulu. The analysis used in this study is a structural approach to the Equation Model (SEM) assisted by the SmartPLS application. Based on the research that has been done, the results show a significant positive effect between the variables of Employee Competence on Organizational Commitment. There is a significant positive effect between the Perceived Organizational variables on Organizational Commitment. There is a significant positive effect between the variables of Employee Competence on Performance. There is a significant positive influence between Perceived Organizational on Performance. There is a significant positive effect between performance on organizational commitment. There is a significant positive effect between the variables of Employee Competence on Organizational Commitment mediated by employee performance. there is a significant positive influence between Perceived Organizational and Organizational Commitment mediated by employee performance.